Modelaje de proteínas de Mycobacterium tuberculosis relacionadas a su defensa frente al estrés oxidativo - Solis Calero, Christian (2005)
This work uses bioinformatics tools and free online access to genomic information in order to identify and characterize proteins related to oxidative stress defense of Mycobacterium tuberculosis, in order to disco ver new appropriate pharmacological targets against this pathogen. Sequences of amino acids of proteins expressed with that function, products of the expression of the genes katG, sodA, sodC, ahpC, ahpD and mgtC were compared with the genome of Mycobacterium tuberculosis H37Rv through the NCBI server National for Center Biotechnology Information), determining their possible redundancy in the genome. Parallely, information was obtained above of their evolutive conserved sequences by global multiply alignment using MAXHOM program, as well models of their threedimensionalstructures by comparative modeling method through the Swiss-model server, or using «recognition of folding» method (threading) through the GENESILICO metaserver. By genomic analysis, proteins codified by katG, ahpD and mgtC genes would be very good candidates to be pharmacological targets due to absence of redundancy in the genome of Mycobacterium tuberculosis as well as similarity with any codified protein by human genes.